Vitamin B-12 Concentrations in Breast Milk Are Low and Are Not Associated with Reported Household Hunger, Recent Animal-Source Food, or Vitamin B-12 Intake in Women in Rural Kenya. Issue 5 (13th April 2016) - Williams, Anne M; Chantry, Caroline J; Young, Sera L; Achando, Beryl S; Allen, Lindsay H; Arnold, Benjamin F; Colford, John M; Dentz, Holly N; Hampel, Daniela; Kiprotich, Marion C; Lin, Audrie; Null, Clair A; et al.
Abstract: Background: Breast milk vitamin B-12 concentration may be inadequate in regions in which animal-source food consumption is low or infrequent. Vitamin B-12 deficiency causes megaloblastic anemia and impairs growth and development in children. Objective: We measured vitamin B-12 in breast milk and examined its associations with household hunger, recent animal-source food consumption, and vitamin B-12 intake. Methods: In a cross-sectional substudy nested within a cluster-randomized trial assessing water, sanitation, hygiene, and nutrition interventions in Kenya, we sampled 286 women 1–6 mo postpartum. Mothers hand-expressed breast milk 1 min into a feeding after 90 min observed nonbreastfeeding. The Household Hunger Scale was used to measure hunger, food intake in the previous week was measured with the use of a food-frequency questionnaire (FFQ), and vitamin B-12 intake was estimated by using 24-h dietary recall. An animal-source food score was based on 10 items from the FFQ (range: 0–70). Breast milk vitamin B-12 concentration was measured with the use of a solid-phase competitive chemiluminescent enzyme immunoassay and was modeled with linear regression. Generalized estimating equations were used to account for correlated observations at the cluster level. Results: Median (IQR) vitamin B-12 intake was 1.5 μg/d (0.3, 9.7 μg/d), and 60% of women consumed <2.4 μg/d, the estimated average requirement during lactation. Median (IQR) breast milk vitamin B-12 concentration was 113 pmol/L (61, 199 pmol/L); 89% had concentrations <310 pmol/L, the estimated adequate concentration. Moderate or severe hunger prevalence was 27%; the animal-source food score ranged from 0 to 30 item-d/wk. Hunger and recent animal-source food and vitamin B-12 intake were not associated with breast milk vitamin B-12 concentrations. Maternal age was negatively associated with breast milk vitamin B-12 concentrations. Conclusion: Most lactating Kenyan women consumed less than the estimated average requirement of vitamin B-12 and had low breast milk vitamin B-12 concentrations. We recommend interventions that improve vitamin B-12 intake in lactating Kenyan women to foster maternal health and child development. The main trial was registered at clinicaltrials.gov as NCT01704105.